METHODOLOGY OF TEACHING STUDENTS TO OVERCOME BARRIERS IN BUSINESS COMMUNICATION - Kraynyak, Lyudmyla (Mountain School of Ukrainian Carpaty, 2023)
The article concerns effective communication as an essential component of business success. The aim of research is to identify the specific communication barriers that students encounter in business contexts, such as cultural differences, language proficiency, and technological challenges; to develop effective teaching methodologies and techniques that can help students overcome these communication barriers, such as intercultural training, language instruction, and the use of technology. It was highlighted that effective communication is vital for business success, and communication barriers such as cultural differences, language, and technology can hinder effective communication. When communication barriers exist, it can have a significant negative impact on a business's performance. Therefore, it is crucial for educators to teach students how to overcome barriers in business communication. The author claims that communication barriers are obstacles that prevent people from effectively conveying and receiving information. Consequently, there are many types of communication barriers, including language barriers, cultural differences, physical barriers, emotional barriers, and perceptual barriers. It has been suggested the methodology for teaching students how to overcome barriers in business communication containing exact steps. The methodology outlined in this article, which includes identifying communication barriers, developing intercultural communication skills, enhancing language proficiency, teaching effective use of technology, and providing feedback, can help students develop the necessary skills to overcome communication barriers in a business setting. It has been stated that developing intercultural communication skills takes time and effort. It requires an open mind, willingness to learn, and respect for cultural differences. The author concludes that the field of teaching students to overcome barriers in business communication is dynamic and evolving, and there is significant potential for further research to enhance our understanding of effective teaching practices in this area.